IMPLEMENTASI TRAUMA HEALING METODE BERMAIN(PETAK UMPET) PASCA ERUPSI SEMERU PADA SISWA SDN SUPITURAANG 01 KECAMATAN PRONOJIWO KABUPATEN LUMAJANG - Aisyah, Siti; Badriyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Indonesia is a country highly prone to natural disasters, including volcanic eruptions, which not only cause physical damage but also have significant psychological impacts, particularly on elementary school-aged children. Children affected by the eruption of Mount Semeru at SDN Supiturang 01 exhibited various trauma symptoms such as excessive anxiety, fear of the surrounding environment, decreased learning concentration, and withdrawal from social interactions. This study aims to describe the implementation of trauma healing through the traditional hide-and-seek game and to analyze its impact on the psychological recovery of children after the disaster. This research employed a qualitative approach with a phenomenological paradigm and a descriptive method. Data were collected through observation, interviews, and documentation involving the school principal, teachers, facilitators, parents, and students. The findings indicate that trauma healing through the hide-and-seek game, conducted in several stages—preparation, opening, implementation, and closing—successfully created a safe and enjoyable environment for children. This method helped children express emotions naturally, reduce anxiety, rebuild self-confidence, enhance social interaction, and improve learning concentration. In addition, the hide-and-seek game contributed to children’s social, emotional, and character development. Therefore, trauma healing based on traditional games is proven to be effective and appropriate to be integrated into post-disaster psychosocial recovery programs in elementary schools, particularly in disaster-prone